Law Enforcement by the Civil Service Police Unit (Satpol PP) in Addressing Street Vendors' Violations of the Regional Regulations of Palembang City Through a Humanistic and Restorative Approach - Abdul Jafar; Sarah Sarah (Journal of Creative Power and Ambition (JCPA), 2026)
Street vendors (Pedagang Kaki Lima or PKL) contribute significantly to local economic development and community livelihoods in Palembang City. However, their activities often conflict with regional regulations governing public order and the use of public spaces, creating challenges for law enforcement authorities. This study aims to analyze the law enforcement efforts undertaken by the Palembang City Civil Service Police Unit (Satpol PP) in addressing violations committed by street vendors through humanistic and restorative approaches. The research employs a normative legal method supported by primary data using a descriptive-analytical approach. Data were collected through literature review, analysis of statutory regulations, and examination of law enforcement practices implemented by the Palembang City Civil Service Police Unit. The findings reveal that law enforcement has been carried out through preventive, persuasive, and proportionate repressive measures. Humanistic enforcement is reflected in legal education, dialogue, guidance, warning letters, and relocation opportunities, while the restorative approach emphasizes restoring public order without disregarding the economic rights of street vendors. Effective enforcement therefore requires collaboration between legal authorities, local government, and community empowerment programs to achieve sustainable public order and social justice.